2001
DOI: 10.1136/sti.77.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytology smears in sexually transmitted infection clinics in the United Kingdom

Abstract: on behalf of the British Co-operative Clinical GroupObjectives: To determine the current practice of smear taking in sexually transmitted infection (STI) clinics within the United Kingdom; what proportion of smears are taken within the national guidelines; whether clinics are screening women not covered by the national screening programme. To compare the abnormality rates of routine and opportunistic (that is, in addition to the screening recommendations) smears; the abnormality rates of smears taken within ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Testing more often than the recommended screening interval (sporadic opportunistic testing) was examined in a UK study performed in clinics focused on sexually transmitted infections [ 13 ]. The authors found that sporadic opportunistic smears had marginally significantly increased rates of LSIL abnormalities but lower (not statistically significant) HSIL abnormalities than routine smears and concluded that there was no reason to depart from recommended screening intervals [ 13 ]. Their findings are in line with our results except that we identified no differences in cytological abnormalities between sporadic opportunistic cytologies and cytologies taken after invitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing more often than the recommended screening interval (sporadic opportunistic testing) was examined in a UK study performed in clinics focused on sexually transmitted infections [ 13 ]. The authors found that sporadic opportunistic smears had marginally significantly increased rates of LSIL abnormalities but lower (not statistically significant) HSIL abnormalities than routine smears and concluded that there was no reason to depart from recommended screening intervals [ 13 ]. Their findings are in line with our results except that we identified no differences in cytological abnormalities between sporadic opportunistic cytologies and cytologies taken after invitation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have argued that opportunistic testing is not cost effective and should not be performed [ 9 , 13 , 14 ], but the significance of opportunistic testing in detecting precancerous cervical lesions remains unclear. Furthermore, many countries suffer from low participation rates in their systematic screening programs [ 15 ], which reduces the effect of the programs.…”
Section: Introductionmentioning
confidence: 99%
“…One of the limitations of this study is that no diagnostic tests were used to validate the selfreported prevalence of RTIs; our estimates were based on syndromic management of curable sexually transmitted infections and other RTIs, a method recommended by the World Health Organization for low-resource settings [2,40]. However, in the absence of a laboratory diagnostic to accompany the analysis reported, this work may greatly underestimate or overestimate RTI prevalence and the true burden of RTIs.…”
Section: Plos Onementioning
confidence: 99%
“…This is similar to a Dublin GU/STD clinic (22%) [ 8 ]. It is reported that GUM patients have a higher rate of cytological abnormalities [ 9 ]. A request to abandon "opportunistic" screening in the Mid West region outside of the Irish Cervical Screening Programme (ICSP) prompted this audit.…”
Section: Introductionmentioning
confidence: 99%